QUALITY BY DESIGN (QBD) AS A TOOL FOR THE OPTIMIZATION OF INDOMETHACIN FREEZE-DRIED SUBLINGUAL TABLETS: IN VITRO AND IN VIVO EVALUATION - IBRAHIM, MERVAT SHAFIK; ELMAHDY ELSAYYAD, NIHAL MOHAMED; SALAMA, ABEER; NOSHI, SHEREEN H. (International Journal of Applied Pharmaceutics, 2021)
Objective: This study aims to prepare and optimize indomethacin freeze-dried sublingual tablets (IND-FDST) by utilizing a quality by design (QbD) approach to achieve rapid drug dissolution and simultaneously bypassing the GIT for better patient tolerability. Methods: A screening study was utilized to determine the most significant factors which the quality attributes, namely disintegration time and % friability. Then an optimization study was conducted using a full response surface design to determine the optimized formula by varying the amount of the matrix-forming polymer (gelatin) and super disintegrant (croscarmellose sodium (CCS)). The variables' effect on the % friability, disintegration time, wetting time, and amount of drug release after 10 min (%Q10) was studied. The optimized formula was tested for compatibility, morphology as well as stability studies under accelerated conditions in addition to the in vivo pharmacodynamics in rats. QbD was adopted by utilizing a screening study to identify the significant formulation factors followed by a response surface optimization study to determine the optimized IND-FDST formulation. Results: Optimized IND-FDST comprised of gelatin/CCS combination in a ratio of 1:1 possessed adequate %friability (0.73±0.03%), disintegration time (25.40±1.21 seconds), wetting time (3.49±0.68 seconds), and % Q10 (100.99±5.29%) as well as good stability under accelerated conditions. IND-FDST also showed significant inhibition of edema, tumour necrosis factor-alpha, and interleukin-6 release in vivo compared to the oral market product by 70%, 42%, and 65%, respectively. Conclusion: QbD presents a successful approach in the optimization of a successful IND-FDST formula that showed superior in vivo and in vitro characteristics.